Diocesan historical archives in Poland. The process of formation - Dębowska, Maria (Archiwa, Biblioteki i Muzea Kościelne, 2015)
In the literature on historical archives of the Catholic Church in Poland there is no scholarly monograph devoted to them. The only textbook is the one written by H.E. Wyczawski, Przygotowanie do studiów w archiwach kościelnych (Preparing for studies in church archives). The publications, appearing after the war, did not present any theoretical fi ndings which could be applied in church archival studies (it refers to developing the theoretical decisions on creating archival fonds, their names etc.), but they certainly provided the impetus and encouragement to continue the action which was initiated before the war. The program developed in the interwar period was adjusted to the new conditions; emphasis was put on practical guidelines for activities related to the founding and functioning of a historical archive in the diocese.